Analysis of Total Quality Management (TQM) Implementation in Improving Human Resource Performance at Amanah Edu Centre Banyuwangi - Liana Widasari Parawangsa Sanjaya; Windy Ellysa; Adinda Dwi Astuti; Fitriatus Soleha; Elok Rosyidah (Best Journal of Administration and Management, 2025)
This study aims to analyze the implementation of Total Quality Management (TQM) in improving human resources (HR) performance at Amanah Edu Centre Banyuwangi. The research uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation. The results show that the implementation of TQM principles, including customer focus, continuous improvement, education and training, as well as employee involvement and empowerment, can enhance the work quality, knowledge, reliability, initiative, and cooperation of HR. Therefore, TQM plays an important role in improving HR performance and the quality of early childhood education services.